2011
DOI: 10.3109/03602532.2011.597401
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivosmall intestinal metabolism of CYP3A and UGT substrates in preclinical animals species and humans: species differences

Abstract: Intestinal first-pass metabolism has a great impact on the bioavailability of cytochrome P450 3A4 (CYP3A) and/or uridine 5'-diphosphate (UDP)-glucoronosyltranferase (UGT) substrates in humans. In vitro and in vivo intestinal metabolism studies are essential for clarifying pharmacokinetics in animal species and for predicting the effects of human intestinal metabolism. We review species differences in intestinal metabolism both in vitro and in vivo. Based on mRNA expression levels, the major intestinal CYP3A is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 148 publications
1
60
1
Order By: Relevance
“…Alternatively, it may reflect significant differences in DMEs expressed across species in the gut wall. Certainly, metabolism studies in preclinical species have reported marked differences when compared to human, depending upon the CYP450 subfamily of interest (79). This highlights an ongoing challenge associated with interpretation of complex in vivo data, in particular, quantifying the exact contribution of intestinal metabolism indirectly from more conventional IV and oral dosing strategies (30,71).…”
Section: Is the Extent Of Intestinal Metabolism Predictable And Can Imentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, it may reflect significant differences in DMEs expressed across species in the gut wall. Certainly, metabolism studies in preclinical species have reported marked differences when compared to human, depending upon the CYP450 subfamily of interest (79). This highlights an ongoing challenge associated with interpretation of complex in vivo data, in particular, quantifying the exact contribution of intestinal metabolism indirectly from more conventional IV and oral dosing strategies (30,71).…”
Section: Is the Extent Of Intestinal Metabolism Predictable And Can Imentioning
confidence: 99%
“…With raloxifene, very high extraction was observed in human intestines whereas moderate extraction was reported in rat (86). Conversely, with morphine, moderate extractions were seen in both rats and humans (79). Recently, Furukawa and co-workers assessed the in vivo intestinal availability of several human UGT substrates across rat, dog, monkey and humans (87).…”
Section: Is the Extent Of Intestinal Metabolism Predictable And Can Imentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse CYP3A11 is homologous to human CYP3A4 and is constitutively expressed in the liver of adult mice, wherein it plays a central role in drug metabolism (Sakuma et al, 2000;Li et al, 2009). CYP3A13 is upregulated in the small intestine and has important effects on drug metabolism in the gastrointestinal tract (Martignoni et al, 2006;Komura and Iwaki, 2011). Mouse CYP3A16 corresponds to human CYP3A7.…”
Section: Introductionmentioning
confidence: 99%